ESG Implementation in the International Financial System: A Literature Review of Challenges, Opportunities, and Global Standards - Ariq Farhan Widiyanto; Dharma Adita; Liya Megawati (Journal Informatic, Education and Management (JIEM), 2026)
This study examines the implementation of Environmental, Social, and Governance (ESG) principles in the international financial system as part of the global transformation toward sustainable economics. ESG serves as a strategic framework integrating environmental, social, and corporate governance dimensions into investment and financing decision-making across nations. The study employs a literature review method with a qualitative descriptive-conceptual approach, aiming to identify challenges, opportunities, and directions for harmonizing global ESG standards. Findings indicate that ESG implementation at the international level still faces several challenges, including inconsistent reporting standards, limited non-financial data, and low institutional readiness in developing countries. Nevertheless, opportunities for harmonization are growing through the establishment of the International Sustainability Standards Board (ISSB) and the implementation of Indonesia’s Sustainable Finance Roadmap Phase II (2021–2025) by the Financial Services Authority (OJK). ESG has been shown to positively influence corporate reputation, financial performance, and long-term financial stability. Therefore, effective ESG implementation requires synergy among governments, international institutions, and the private sector to realize a transparent, inclusive, and sustainable global financial system.